Hubungan Faktor Pemberian ASI Eksklusif dengan Kejadian Stunting Pada Anak Balita - Sudrayani Usman; Syahrul Ramdhan (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; stunting is a growth disorder caused by insufficient nutritional intake for a long time. Objectives; know the factors of exclusive breastfeeding on the incidence of stunting in children under five. Method; The design of this research is a literature review. Result; shows that there are similarities in the results of the 3 journals reviewed, namely there is a relationship between exclusive breastfeeding and the incidence of stunting in children under five. Conclusion; that there is a relationship between exclusive breastfeeding and the incidence of stunting in children under five, therefore it is necessary to encourage health workers to mothers under five to provide sufficient knowledge and understanding in order to be able to breastfeed exclusively.